Psalme-Blade til Kirke-Bod. En brevveksling mellem Grundtvig og hans præstevenner i foråret 1843 - Holm, Jette (Grundtvig-studier, 2002)
Psalme-Blade til Kirke-Bod. En brevveksling mellem Grundtvig og hans præstevenner i foråret 1843 » Psalmeblade til Kirke-Bod« [Hymn-pages to the Church 's enhancement]. Correspondence between Grundtvig and his clerical friends, Spring 1843 By Jette Holm Grundtvig’s sermons from the 1840s are in process of transcription in the Centre for Grundtvig Studies, Aarhus University. The first three years together with a volume of annotations will be published by Forlaget Vartov in September 2003, to coincide with the University’s seventy-fifth anniversary.In 1843 Gr drafted a supplement to the hymnal - Psalmeblade til Kirke-Bod [Hymn-pages to the Church 's enhancement] - as a counterstroke to Bishop Mynster’s Udkast til et Tillæg til den evangelisk-christelige Psalmebog. (Foreløbig udgivet som Prøve) [Draft ofa Supplement to the evangelical-Christian Hymnal (Provisionally issued for trial)] (Copenhagen, 1843).Since Gr’s sermons and hymns belong inseparably together it has seemed fitting to examine this supplement to the hymnal more closely, in association with the editing of the sermons.Gr worked on Psalmeblade til Kirke-Bod from Spring 1843 through to his departure for England on 7 June 1843. The letters here presented are of invaluable significance in shedding light upon this undertaking, for Gr asked his clerical friends Peter and Ferdinand Fenger, Gunni Busck and Peter Rørdam for recommendations of hymns which he earnestly promised to include in his considerations.Examination of the published editions of the Gr-correspondence reveals that Gr’s own letters have all been put into print, but that the majority of the letters from these clerical friends have never been published. This means, for example, that the quite crucial lists of hymns are lacking.In order to remedy this want, so that research into the hymns can follow at first hand the dialogue between Gr and his friends, this correspondence from the Spring of 1843 is now published.The letters include interesting topics such as Gr’s views upon translations and upon the new hymns of Ingemann. Gr’s own re workings of the hymns of Kingo are discussed, and an insight is afforded into his own relationship with the Lutheran tradition.Peter Fenger thinks that the new hymns (Gr’s own!) ought to make way for the old, if considerations of space should make it necessary. To this Gr replies that certainly the old tried and proven hymns are the most important where the festivals and general edification are concerned, but not with respect to baptism nor to the living foundation and understanding of the Church: »because this was the weak side of the old ones, which is in serious need of strengthening.« Gr emphasises to Gunni Busck that the King’s commission refers to »the old and more recent hymns« - so there must also be room for some of his own new hymns from his Sang-Værk til den danske Kirke (1836-37). Various completely new hymns are written during the work upon Psalmeblade til Kirke-Bod.Peter Rørdam recommends the tunes of the heroic ballads for use as hymnmelodies, but he gets a lecture from Gr on the difference between church and school. There is as a whole a great problem with the melodies, because for the most part Gr’s hymns had never been sung.By the beginning of May 1843 Gr has almost completed his supplement. He has arranged to meet the Fenger brothers and Gunni Busck when the Queen, Caroline Amalie, offers him a journey to England. This puts an end to work on the little hymnal-supplement. In the course of the summer Peter Fenger copies out the supplement - fortunately, since this is the only exemplar which survives. It is expected that an annotated edition of Psalmeblade til Kirke-Bod will be published in due course.